Analisis Reformasi Birokrasi Dalam Meningkatkan Kinerja Pegawai Pada Badan Pendapatan Daerah Kabupaten Kaimana (Soetomo Magister Ilmu Administrasi, 2023)
One of the main factors that play a role in the realization of a clean government and good leadership is the bureaucracy. Bureaucracy reform is crucial in enhancing employee performance which impacts more efficient public services aligned with the needs of the community. This research is motivated by the role of bureaucracy reform and employee performance. The purpose of this study is to identify and analyze the partial effects of Change Management, Structuring HR Management System, Organizational Capacity and Accountability, and Public Service Quality on Employee Performance at the Regional Revenue Agency of Kaimana Regency. This research employs a Qualiitative Descriptive Approach. Data collection technique involves the use of interview, observation and documentation. The research findings indicate that Change Management, Structuring HR Management System, Organizational Capacity and Accountability, as well as Public Service Quality, individually have a significant influence on Employee Performance at the Regional Revenue Agency of Kaimana Regency. Keywords: Bureucracy Reformation, And Employee Performance